Iminosugars counteract the downregulation of the interferon gamma receptor by dengue virus - Miller, J; Hill, M; Brun, J; Pountain, A; Sayce, A; Zitzmann, N (Elsevier, 2019)
The antiviral mechanism of action of iminosugars against many enveloped viruses is hypothesized to be a consequence of misfolding of viral N-linked glycoproteins through inhibition of host endoplasmic reticulum alpha-glucosidase enzymes. Iminosugar treatment of dengue virus (DENV) infection results in reduced secretion of virions and hence lower viral titres in vitro and in vivo. We investigated whether iminosugars might also affect host receptors important in DENV attachment and uptake and immune responses to DENV. Using a primary human macrophage model of DENV infection, we investigated the effects of maturation with IL-4, DENV-infection and treatment with N-butyl-1-deoxynojirimycin (NB-DNJ) or N-(9-methoxynonyl)-1-DNJ (MON-DNJ) on expression of 11 macrophage receptors. Whereas iminosugars did not affect surface expression of any of the receptors examined, DENV infection significantly reduced surface IFN gamma receptor amongst other changes to total receptor expression. This effect required infectious DENV and was reversed by iminosugar treatment. Treatment also affected signalling of the IFN gamma receptor and TNF alpha receptor. In addition, iminosugars reduced ligand binding to the carbohydrate receptor-binding domain of the mannose receptor. This work demonstrates that iminosugar treatment of primary macrophages affects expression and functionality of some key glycosylated host immune receptors important in the dengue life cycle.